High‐Q and Tailorable Fano Resonances in a One‐Dimensional Metal‐Optical Tamm State Structure: From a Narrowband Perfect Absorber to a Narrowband Perfect Reflector. (19th April 2021) - Wang, Zhiyu; Ho, Ya‐Lun; Cao, Tun; Yatsui, Takashi; Delaunay, Jean‐Jacques
Abstract: Fano resonances giving rise to a rich variety of asymmetric spectral shapes have been investigated in optical nanostructures with multidimensional configurations. However, 1D nanostructure realizing Fano resonances with well‐controlled spectral shapes are yet to be demonstrated. Here, the authors present both numerically and experimentally a 1D nanostructure exhibiting rich Fano resonances induced by interference between a lossy background (continuum) provided by a metal thin film and a discrete optical Tamm state (OTS). A drastic change in the Fano line shape occurs from a narrowband perfect absorber into a narrowband perfect reflector by controlling the metal thin film. Independent from the metal‐related Fano profile, the OTS component determines the resonance frequency and guarantees a sharp resonance (with quality factors over 1000) on the flat mirror background. Taking advantage of its high‐ Q property, the structure can be developed into a dispersion device with subnanometer spectral resolution, which even enables a direct imaging of spectral information of molecular fingerprint. The authors believe that this work not only demonstrates a planar nanostructure with versatile Fano resonances for various applications but also provides physical insights into how a metal thin film can induce and significantly affect the Fano resonances in 1D optical resonators. Abstract : The investigated 1D structure consists of a thin metal film on top of an OTS resonator (DBR1 + DBR2 ). A wide range of Fano line shapes (in absorptance spectra) with a narrow bandwidth ( Q above 1000) can be obtained (from narrowband perfect absorber to narrowband perfect reflector) by utilizing different metals as the top layer.